The effects of water ingestion on high intensity cycling performance in a moderate ambient temperature - Robinson, Tracy Anne (MRC/UCT RU for Exercise and Sport Medicine, 2018)
Eight endurance~trained cyclists rode as far as possible in 1 h on a stationary cyclesimulator in a moderate environment (20°C, 60% relative humidity, 3 m/s wind speed) while randomly receiving either no fluid (NF) or attempting to replace their ~1.7 l sweat loss measured in a previous 1 h familiarisation performance ride at ~85% of peak oxygen uptake (VO₂ peak) with artificially sweetened, coloured water (F). During F the cyclists drank 1.49 ± 0.14 1 (values are mean± SEM), of which 0.27 ± 0.08 1 remained in the stomach at the end of exercise and 0.20 ± 0.05 1 was urinated after the trial. Thus, only 1.02 ± 0.12 l of the ingested fluid was available to replace sweat losses during the 1 h performance ride. That fluid decreased the average heart rate from 166 ± 3 to 157 ± 5 beats/min (P < 0.0001) and reduced the final serum [Na+] and osmolalities from 143 ± 0.6 to 139 ± 0.6 mEq/1 (P < 0.005) and from 294 ± 1.7 to 290 ± 1.9 mOsm/1 (P = 0.05), respectively. Fluid ingestion did not attenuate rises in plasma anti diuretic hormone and angiotensin concentrations, or decrease the ~-15% falls in estimated plasma volume in the F and NF trials. Nor did fluid ingestion significantly effect the ~1.7 l/h sweat rates, the rises in rectal temperature (~36.6° to 38.3°C) or the ratings of perceived exertion in the two trials. Ingestion of ~1.5 l of fluid produced an uncomfortable stomach fullness and reduced the distance covered in 1 h from 43.1 ± 0. 7 to 42.3 ± 0.6 km (P<0.05). Thus, trying to replace > 1.0 l/h sweat losses during high-intensity, short duration exercise in a moderate environment does not induce beneficial physiological effects, and may impair exercise performance.